The Impact of Social Media Towards Students English Speaking Proficiency at English Department of University - Weldy Basongan; Charlie Baka; Nilma Taula’bi’; Markus Deli Girik Allo (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this study is to determine the impact of using social media on students' speaking skills at Universitas Kristen Indonesia Toraja. This research use qualitative method. The purposive sampling use to obtain data from 7th semester students of English education. Data collected by interview and observation. The result of this research is Instagram social media has an effect on speaking fluency, vocabulary improvement, grammar and pronunciation. The impact fell by students experienced a significant increase in fluency, pronunciation and understanding of informal language use. The use of Instagram social media can personalize students' experience to practice speaking and listening skills and even motivate and increase self-confidence. Social media can provide a positive experience for students by offering engaging, interactive, and supportive content for English language learning, so it is worth considering using social media in education.